Starch biodegradation in a lignin modified slow release fertilizer: Effect of thickness - Majeed, Z. (Trans Tech Publications Ltd, 2014)
Biopolymers and their modified blends are naturally biodegradable materials being intensively used in control nutrient release formulations. Material biodegradability varies with thickness which further effect natural decay when applied in soil. Preliminary study was conducted for a urea-nitrogen incorporated slow release fertilizer (SRF) prepared with 0.27mm, 0.54mm and 1.03mm thickness. The starch biodegradation was decreased with increased in thickness both in non-sterile flooded soil (NSF) and sterile flooded soil (SF). NSF soil data was corrected with SF soil (as control) showed improved exponential decay constant and half-life estimates compared to NSF soil only. Study concludes that SRF thickness is important parameter increases half-life and reduces starch biodegradability in SRF. Â© 2014 Trans Tech Publications, Switzerland.